2019
DOI: 10.3389/fneur.2019.00636
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Effect of Exercise on Neuropathic Pain Induced by Peripheral Nerve Injury in Rat Models

Abstract: Background: There is accumulating evidence showing that exercise therapy may play an active role in peripheral neuropathic pain (NP). However, there have been no meta-analysis to investigate the effects of exercise on NP induced by peripheral nerve injury in rat models. Methods: PubMed, EMBASE, and Web of Science were searched from inception to January 2019. A random-effect model was implemented to provide effect estimates for pain-related behavioral test outcome. Mean differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
(118 reference statements)
0
23
0
Order By: Relevance
“…In general, aerobic exercise protocols reduce exaggerated responses (i.e., hypersensitivities) to these tests. In fact, recent metaanalyses concluded exercise training reduced nociceptive responses to mechanical and thermal tests compared to no exercise controls in animal models of peripheral nerve injury (i.e., SNI and DPN) [56] and SCI [57].…”
Section: Preclinical Evidencementioning
confidence: 99%
“…In general, aerobic exercise protocols reduce exaggerated responses (i.e., hypersensitivities) to these tests. In fact, recent metaanalyses concluded exercise training reduced nociceptive responses to mechanical and thermal tests compared to no exercise controls in animal models of peripheral nerve injury (i.e., SNI and DPN) [56] and SCI [57].…”
Section: Preclinical Evidencementioning
confidence: 99%
“…Treatment with mirogabalin (3–10 mg/kg) relieves nerve injury-related anxiety-type behaviors and tactile allodynia ( Murasawa et al., 2020 ), suggesting that reduction of neuropathic pain could lead to a reduction of the comorbidities. Pre-clinical studies have suggested that forced physical exercise decreases neuropathic pain in rodents ( Kuphal et al., 2007 ; Chen et al., 2012 ; Groover et al., 2013 ; Guo et al., 2019 ). Exercise improves physical function and fibromyalgia symptoms ( Schachter et al., 2003 ).…”
Section: Effects Of Metformin On Painmentioning
confidence: 99%
“…The 2 main types of exercises examined in the preclinical literature are aerobic (eg, running and swimming) and passive neurodynamic treatments. There is convincing evidence that aerobic exercise not only reverses established neuropathic pain, 31 but also prevents its development. 29 Aerobic exercise seems more beneficial than resistance exercise for motor nerve regeneration and functional recovery, although this remains to be confirmed for sensory measures.…”
Section: Implications For Practice Remaining Challenges and Potementioning
confidence: 99%
“… 35 The beneficial effects of aerobic exercises have been attributed to a regulation of inflammatory cytokines, neurotrophins, neurotransmitters, endogenous opioids, ion channel function, and descending inhibition as well as axonal and myelin regeneration capacity. 31 , 40 Intriguingly, the neuroprotective benefits of aerobic exercise are influenced less by the type of exercise (eg, swimming vs running) than by other variables. For example, exercise dosage affects neuroprotection: it seems that low-to-moderate intensity exercise is neuroprotective but moderate-to-high intensity exercise can be neurotoxic.…”
Section: Implications For Practice Remaining Challenges and Potementioning
confidence: 99%